Decline of Admission for Acute Coronary Syndromes and Acute Cardiovascular Conditions during COVID-19 Pandemic in Veneto Region - Marco Zuin; Giacomo Mugnai; Alberto Zamboni; Edlira Zakja; Roberto Valle; Giovanni Turiano; Sakis Themistoclakis; Daniele Scarpa; Salvatore Saccà; Loris Roncon; Francesca Rizzetto; Paola Purita; et al. (Viruses, 2022)
Background: The present study aimed to examine longitudinal trends in hospitalizations for acute coronary syndrome (ACS) before and during the COVID-19 pandemic, by reviewing the data from 13 hospitals of the Veneto Region, in the north-east of Italy. Methods: We performed a multicenter, retrospective analysis including all the consecutive patients presenting with ACS and other acute cardiovascular (CV) conditions (defined as heart failure, arrhythmias, cardiac arrest and venous thromboembolism) hospitalized in 13 different hospitals of the Veneto Region covering a population of 2,554,818 inhabitants, during the first (between 15 March 2020 and 30 April 2020) and second (between 15 November 2020 and 30 December 2020) COVID-19 pandemic waves (the 2020 cohort). Data were compared with those obtained at the same time-windows of years 2018 and 2019 (the historical cohorts). Results: Compared to the historical cohorts, a significant decrease in the number of ACS cases was observed in 2020 (−27.3%, p = 0.01 and −32%, p < 0.001, comparing 2018 versus 2020 and 2019 and 2020, respectively). The proportion of patients hospitalized for acute CV conditions decreased during the first and second wave COVID-19 pandemic when compared to the historical cohorts (−36.5%, p < 0.001 and −40.6%, p < 0.001, comparing 2018 versus 2020 and 2019 and 2020, respectively). Pearson’s correlation evidenced a significant inverse relationship between the number of COVID-19 cases and both ACS hospital admissions (r = −0.881, p = 0.005) and hospitalizations for acute CV conditions (r = −0.738, p = 0.01), respectively. Conclusions: The decrease in hospitalizations for ACS and other acute CV conditions will strongly affect future patients’ management since undiagnosed nonfatal CV events represent a source of increased (and unknown) CV morbidity and mortality.